Effect of Concentration and Time of Chitosan Application on The Growth of Pineapple (Ananas comosus) - Endang Yuniastuti; Salsabila Tiara Putri; Gani Cahyo Handoyo (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2024)
Pineapple (Ananas comosus) is a popular fruit crop in Indonesia. Pineapple crowns are one of the planting materials used in pineapple cultivation, but their growth is slower than other planting materials, so that the addition of chitosan is needed, which has the potential to stimulate growth. This study aims to determine the best concentration and application time of chitosan that can improve pineapple growth. The study was conducted in the screenhouse of the Faculty of Agriculture, Sebelas Maret University, Surakarta during March-June 2025 with a Completely Randomized Design (CRD) with two factors, namely chitosan concentration (without chitosan, 1 ppm, 3 ppm, 5 ppm) and time of chitosan application (morning, afternoon, morning and afternoon). Each treatment was repeated 4 times, resulting in 48 experimental units. The results showed that no combination of concentration and time of chitosan application was found to simultaneously increase pineapple growth. The treatment concentration of 1 ppm and 3 ppm gave the best result to increasing leaf number; concentration 1 ppm, 3 ppm, and 5 ppm gave the best result to increasing total leaf area and longest root length. Time of chitosan application once in the morning or evening gave the best result to increasing photosynthesis rate and stomatal conductance. Chitosan has the potential as a biostimulant for plant growth and is effective in increasing the physiological activity of plants.